Peran Guru IPS dalam Mengoptimalkan Keaktifan Belajar Siswa Melalui Model Pembelajaran Active Learning di SMPN 3 Srengat Blitar - Agustina Zahrotin Nisak; Yudi Krisno Wicaksono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study explores the role of Social Studies (IPS) teachers in optimizing students’ learning activeness through the implementation of the Active Learning model at SMPN 3 Srengat Blitar. The background of this study includes issues such as students’ lack of discipline when entering the classroom, classroom attitudes and habits that hinder the learning process, and the use of monotonous and less engaging teaching methods. The purpose of this research is to examine the role of IPS teachers, the impact of implementing Active Learning, the challenges teachers face, and institutional support provided by the school in enhancing student engagement. A descriptive qualitative approach was used with a case study design. Data were collected through observation, in-depth interviews, and documentation involving teachers, students, and school authorities. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The validity of the data was ensured through triangulation of sources, techniques, and theories. The results indicate that IPS teachers actively serve as facilitators and motivators in implementing Active Learning strategies, such as group discussions, student presentations, and the use of interactive media. The application of this model increased student participation, encouraged self-expression, and enhanced classroom engagement. Despite challenges such as time constraints and varying student readiness, school support significantly contributed to the successful implementation of this approach. Thus, Active Learning is proven to be effective in creating an engaging and student-centered learning environment, aligning with the theory proposed by Bonwell and Eison.